EFL teachers’ creativity in the classroom - Melvina Melvina (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2023)
In the 21st century, teaching and learning English should be creative. The teacher, as the orchestra conductor, is required to be creative in the classroom. The purpose of the present study is to scrutinize English teachers’ creativity when teaching. The concept of a creativity teacher (freedom, positive challenge, supervisory encouragement, group support, sufficient resources, and organizational support) from Amabille (1997) was adopted. This study is carried out in one Junior high school in Tebo Regency. Descriptive research methodology is used. The data was collected through direct communication and analyzed descriptively. The results revealed that the English teacher is creative in the classroom. She has implemented a pleasant learning atmosphere in the teaching and learning process. This study suggests that English teachers should be creative to foster students' creativity in the classroom environment. Keywords: 21st century learning; EFL teacher; teacher creativity